TELAAH PARADIGMA KEILMUAN: Kajian Pandangan Tokoh Tentang Paradigma Keilmuan - Nurul Milla; Hariyanto Hariyanto (LP2M Universitas Ibrahimy, 2016)
Paradigm is a fundamental image of a subject matter from a standpoint of science. Paradigm provides a groove about something that should be studied, what questions that should be presented and what rules that should be followed in that answer of argumentation. Therefore, the paradigm is like a frame that used by peoples to observe the world with their insight (world-view). This study only limited the discussion in the scientific paradigm in the perspectives of Descartes, Camto, Bacon, John Stuart Mill.